Pediatric Insomnia: Update and Future Directions - Medalie, Lisa; Gozal, David (Journal of Child Science, 2018)
Throughout their childhood, pediatric insomnia impacts approximately 25% of all children in the general population. Although it can occur as an isolated condition, it commonly associates with other comorbidities, such as autism, developmental delay, and psychiatric disorders. Careful and detailed history is essential, and sleep logs and actigraphy are useful tools in the assessment and diagnosis of pediatric insomnia. However, polysomnography is usually not warranted in the assessment of pediatric insomnia unless underlying medically-based sleep symptoms are concurrently identified and justify such test. In the majority of cases, behavioral interventions are the recommended approach for treatment. Despite the fact that many pharmacological approaches are used for child insomnia off-label, there are currently no FDA (Food and Drug Administration) approved medications for the management of pediatric insomnia. The high prevalence of pediatric insomnia, coupled with the low number of providers, who are formally trained in behavioral treatment for this prevalent condition, highlights the urgent need for improving primary care practitioner awareness, while expanding alternative routes to access to care, such as interactive virtual technology-based treatments, parent education and manuals, along with ongoing efforts to increase professional training opportunities.
Keywords: pediatric; insomnia; review